A sodium ion battery positive electrode material and its preparation method and application

By preparing the sodium ion battery positive electrode material composed of Nax[NiaCubFecMnd]eMfO2 and adding doped element M to regulate the crystal structure, the problem of unstable structure and low specific capacity of the sodium ion battery positive electrode material is solved, and excellent electrochemical performance and cost reduction are achieved.

CN119764441AInactive Publication Date: 2025-04-04PINGYU ZHONGXING ENERGY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510272374.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The structure of the positive electrode material of sodium ion battery is unstable during charging and discharging, resulting in low specific capacity and poor cycle stability. It is difficult for the prior art to fully realize the regulation of the crystal structure.

Method used

By preparing the sodium ion battery positive electrode material composed of Nax[NiaCubFecMnd]eMfO2, doped elements M (such as Ti, Li, Fe, Mn or F) are added, and the layered oxide crystal structure is adjusted by adjusting the electronegativity of the elements to achieve the transformation between P2 and O3 phases.

Benefits of technology

The electrochemical performance of the positive electrode material of sodium ion battery is improved, the discharge capacity of the first circle is high, the retention rate of 100 cycles is high, and the crystal structure is controllable, reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764441A_ABST
    Figure CN119764441A_ABST
Patent Text Reader

Abstract

The present invention provides a sodium ion battery positive electrode material and a preparation method and application thereof, belonging to the field of battery technology. The sodium ion battery positive electrode material is composed of Na x [Ni a Cu b Fe c Mn d ] e M f O2, M includes Ti, Li, Fe, Mn or F; wherein, 0.67≤x≤1.2, 0≤a<0.3, 0≤b≤0.35, 0≤c≤0.35, 0.1≤d≤0.6, 0.8≤e≤1, 0<f≤0.2, a, b and c are not 0 at the same time, and a+b+c+d=1, e+f=1. The sodium ion battery positive electrode material provided by the present invention has excellent electrochemical properties and a controllable crystal structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a sodium ion battery positive electrode material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries are a potential alternative to lithium-ion batteries due to their low cost and widespread availability of sodium resources, especially in the field of large-scale energy storage. Among the many sodium-ion battery cathode materials, layered oxide materials have been widely explored due to their good electrochemical reversibility, high theoretical capacity and ease of synthesis.

[0003] However, since sodium ions have a larger radius than lithium ions, the positive electrode materials of sodium ion batteries face complex multiple phase changes during the charging and discharging process, which makes their structure more unstable than that of lithium ion battery positive electrode materials and their specific capacity is also lower than that of lithium ion battery positive electrode materials.

[0004] According to the different coordination environments of sodium ions, the crystal structure of layered positive electrode materials is mainly divided into P2-type layered oxide positive electrode materials and O3-type layered oxide positive electrode materials. Among them, when the sodium content is between 0.45 and 0.7 (referring to the sodium ratio), it is a P2-type layered oxide crystal structure. The P2 type is a sodium-deficient compound with a wider interlayer spacing in the crystal structure, so it has an open prismatic channel, which can provide fast ion deintercalation and high structural stability, but its capacity is low; when the sodium content is between 0.75 and 1.2, it is an O3-type layered oxide crystal structure. The O3 type has the advantage of high specific capacity, but the interlayer spacing is smaller, and sodium ion deintercalation is difficult. More energy will be required during the deintercalation process, and the crystal structure will be destroyed. Therefore, the O3-type material has poor structural stability, resulting in poor cycle stability.

[0005] At present, the crystal structure can only be controlled by adjusting the sodium ion content, but it is not possible to completely achieve 100% crystal structure regulation, which leads to poor electrical performance of the prepared sodium ion battery cathode material, such as NaMnO 2 (Sodium content is 1) It is a P2 type layered oxide crystal structure material with a low first cycle discharge capacity of 60~70mA / h / g. Summary of the invention

[0006] In view of this, the object of the present invention is to provide a sodium ion battery positive electrode material and a preparation method and application thereof. The sodium ion battery positive electrode material provided by the present invention has excellent electrochemical properties, and the method provided by the present invention can achieve directional regulation of the layered oxide crystal structure.

[0007] In order to achieve the above object, the present invention provides the following scheme: The present invention provides a sodium ion battery positive electrode material, which is composed of Na x[Ni a Cu b Fe c Mn d ] e M f O 2 , M includes Ti, Li, Fe, Mn or F; wherein, 0.67≤x≤1.2, 0≤a<0.3, 0≤b≤0.35, 0≤c≤0.35, 0.1≤d≤0.6, 0.8≤e≤1, 0<f≤0.2, a, b and c are not 0 at the same time, and a+b+c+d=1, e+f=1.

[0008] Preferably, the sodium ion battery positive electrode material is a layered structure.

[0009] Preferably, the sodium ion battery positive electrode material includes Na 0.85 [Ni 0.23 Cu 0.11 Fe 0.33 Mn 0.33 ] 0.95 Li 0.05 O 2 、Na 0.85 [Ni 0.23 Cu 0.11 Fe 0.33 Mn 0.33 ] 0.95 Ti 0.05 O 2 、Na 0.85 [Ni 0.23 Cu 0.11 Fe 0.33 Mn 0.33 ] 0.95 Fe 0.05 O 2 、Na 0.85 [Ni 0.23 Cu 0.11 Fe 0.33 Mn 0.33 ] 0.95 Mn 0.05 O 2 Or Na 0.85 [Ni 0.23 Cu 0.11 Fe 0.33 Mn 0.33 ] 0.95 F 0.05 O 2 .

[0010] The present invention provides a method for preparing the positive electrode material of a sodium ion battery according to the above scheme, comprising the following steps: Sodium salt, precursor Ni a Cub Fe c Mn d (OH) 2 and a compound containing element M, and sintering to obtain the positive electrode material for a sodium ion battery; wherein 0≤a<0.3, 0≤b≤0.35, 0≤c≤0.35, 0.1≤d≤0.6, a, b and c are not 0 at the same time, and a+b+c+d=1; The element M includes Ti, Li, Fe, Mn or F.

[0011] Preferably, the compound containing element M includes lithium carbonate, titanium dioxide, ferric nitrate, manganese acetate or sodium fluoride.

[0012] Preferably, the sintering temperature is 700-950° C., and the holding time is 8-24 hours.

[0013] Preferably, the sodium salt, the precursor Ni a Cu b Fe c Mn d (OH) 2 The molar ratio of the compound containing element M is (0.67~1.2):(0.8~1):(0~0.2), and is not zero.

[0014] Preferably, the sodium salt comprises sodium carbonate.

[0015] Preferably, the mixing comprises: mixing sodium salt, precursor Ni a Cu b Fe c Mn d (OH) 2 , a compound containing element M and a polar organic solvent are mixed and ground until the polar organic solvent evaporates.

[0016] The present invention provides the sodium ion battery positive electrode material described in the above scheme or the use of the sodium ion battery positive electrode material prepared by the preparation method described in the above scheme in a sodium ion battery.

[0017] The present invention provides a sodium ion battery positive electrode material, which is composed of Na x [Ni a Cu b Fe c Mn d ] e M f O 2, M includes Ti, Li, Fe, Mn or F; wherein, 0.67≤x≤1.2, 0≤a<0.3, 0≤b≤0.35, 0≤c≤0.35, 0.1≤d≤0.6, 0.8≤e≤1, 0<f≤0.2, a, b and c are not 0 at the same time, and a+b+c+d=1, e+f=1.

[0018] The sodium ion battery positive electrode material provided by the present invention has excellent electrochemical properties, a high first cycle discharge capacity, a high cycle retention rate of 100 cycles, and a controllable crystal structure. Specifically, by adding element M, the Na2O3 biphase composed of P2 and O3 can be x Ni a Cu b Fe c Mn d O 2 (0.67≤x≤1.2, 0≤a<0.3, 0≤b≤0.35, 0≤c≤0.35, 0.1≤d≤0.6, and a, b, c are not 0 at the same time, and a+b+c+d=1) into a single phase of P2 (space group is P63 / mmc) or a double phase of P2 and O3 consisting of Na x Ni a Cu b Fe c Mn d O 2 Transformed into O3 single phase (space group is R-3m).

[0019] The method provided by the present invention can realize the directional regulation of the crystal structure of layered oxides. The present invention divides the doping element M into two types of elements with strong electronegativity and weak electronegativity, wherein Ti, Li and Fe are elements with weak electronegativity, and Mn and F are elements with strong electronegativity. The present invention adds the above elements during mixing. When the elements with strong electronegativity are introduced into the system, the mutual repulsion between atoms in the system becomes larger, thereby inducing the Na2O3 dual-phase structure of P2 and O3 in the system. x Ni a Cu b Fe c Mn d O 2 The O3 phase in the system transforms into the P2 phase; when an element with weaker electronegativity is introduced into the system, the repulsion between atoms in the system will be weakened, thus inducing the Na2O3 dual phase in the system. x Ni a Cu b Fe c Mn d O 2When the P2 phase in the system transforms into the O3 phase, the interlayer spacing becomes smaller, and more sodium ions will be deintercalated, so the initial capacity of the battery will become higher. When the O3 phase transforms into the P2 phase, the more Na ions in the O3 phase will be retained. + , but the interlayer spacing becomes wider, so it can make sodium ions easier to insert and remove without deforming the crystal structure, so the cycle stability will be better.

[0020] The preparation method provided by the present invention is simple and improves the comprehensive performance (e.g., first cycle discharge capacity and 100 cycle retention rate) and application potential of the positive electrode material. The sodium ion secondary battery using the positive electrode material of the present invention has a controllable crystal structure and can effectively reduce costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0022] Figure 1 The XRD pattern of the positive electrode material of the O3 type sodium ion battery prepared in Example 1 of the present invention; Figure 2 This is a SEM image of the positive electrode material of an O3 type sodium ion battery prepared in Example 1 of the present invention; Figure 3 XRD diagram of the P2 sodium ion battery positive electrode material prepared in Example 4 of the present invention; Figure 4 This is a SEM image of the P2 type sodium ion battery positive electrode material prepared in Example 4 of the present invention; Figure 5 XRD diagram of the P2 / O3 dual-phase sodium ion battery positive electrode material prepared in Comparative Example 1 of the present invention; Figure 6 This is a SEM image of the P2 / O3 dual-phase sodium ion battery positive electrode material prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0023] The present invention provides a sodium ion battery positive electrode material, which is composed of Na x [Ni a Cu b Fe c Mn d ] e M f O 2, M includes Ti, Li, Fe, Mn or F; wherein, 0.67≤x≤1.2, 0≤a<0.3, 0≤b≤0.35, 0≤c≤0.35, 0.1≤d≤0.6, 0.8≤e≤1, 0<f≤0.2, a, b and c are not 0 at the same time, and a+b+c+d=1, e+f=1.

[0024] The sodium ion battery cathode material of the present invention preferably has a layered structure, and the specific composition includes Na x Ni a Cu b Fe c Mn d O 2 and doped into the Na x Ni a Cu b Fe c Mn d O 2 Element M in the crystal lattice (doped in the transition metal position).

[0025] In the present invention, the sodium ion battery positive electrode material preferably includes Na 0.85 [Ni 0.23 Cu 0.11 Fe 0.33 Mn 0.33 ] 0.95 Li 0.05 O 2 、Na 0.85 [Ni 0.23 Cu 0.11 Fe 0.33 Mn 0.33 ] 0.95 Ti 0.05 O 2 、Na 0.85 [Ni 0.23 Cu 0.11 Fe 0.33 Mn 0.33 ] 0.95 Fe 0.05 O 2 、Na 0.85 [Ni 0.23 Cu 0.11 Fe 0.33 Mn 0.33 ] 0.95 Mn 0.05 O 2 Or Na 0.85 [Ni 0.23 Cu 0.11 Fe 0.33 Mn 0.33 ] 0.95 F 0.05O 2 .

[0026] The sodium ion battery positive electrode material provided by the present invention has excellent electrochemical properties, a high first cycle discharge capacity, a high cycle retention rate of 100 cycles, and a controllable crystal structure. Specifically, by adding element M, the Na2O3 biphase composed of P2 and O3 can be x Ni a Cu b Fe c Mn d O 2 (0.67≤x≤1.2, 0≤a<0.3, 0≤b≤0.35, 0≤c≤0.35, 0.1≤d≤0.6, and a, b, c are not 0 at the same time, and a+b+c+d=1) into a single phase of P2 (space group is P63 / mmc) or a double phase of P2 and O3 consisting of Na x Ni a Cu b Fe c Mn d O 2 Transformed into O3 single phase (space group is R-3m).

[0027] The present invention provides a method for preparing the positive electrode material of a sodium ion battery according to the above scheme, comprising the following steps: Sodium salt, precursor Ni a Cu b Fe c Mn d (OH) 2 and a compound containing element M, and sintering to obtain the sodium ion battery positive electrode material; wherein 0≤a<0.3, 0≤b≤0.35, 0≤c≤0.35, 0.1≤d≤0.6, a, b and c are not 0 at the same time, and a+b+c+d=1; the element M includes Ti, Li, Fe, Mn or F.

[0028] Unless otherwise specified, the raw materials and equipment used in the present invention are commercially available products.

[0029] In the present invention, the sodium salt preferably includes sodium carbonate; the compound containing element M preferably includes lithium carbonate, titanium dioxide, iron nitrate, manganese acetate or sodium fluoride. a Cu b Fe c Mn d (OH) 2 The molar ratio of the compound containing element M is preferably (0.67-1.2):(0.8-1):(0-0.2), and is not 0. In the embodiment of the present invention, it can be specifically 0.85:0.95:0.05.

[0030] In the present invention, the precursor Ni a Cu b Fe c Mn d (OH) 2 It is preferably obtained by purchase or self-production. When self-production is adopted, reference is made to CN116375111A.

[0031] In the present invention, the mixing preferably comprises: mixing sodium salt, precursor Ni a Cu b Fe c Mn d (OH) 2 , a compound containing element M and a polar organic solvent are mixed and ground until the polar organic solvent evaporates.

[0032] In the present invention, the polar organic solvent preferably includes ethanol. The present invention has no particular requirement on the amount of ethanol used, and can a Cu b Fe c Mn d (OH) 2 , and immerse it in the compound containing element M.

[0033] After the mixing is completed, the mixed material is preferably dried; the drying temperature is preferably 120° C. The present invention has no particular requirement for the drying time, as long as the mixed material can be dried.

[0034] In the present invention, the sintering temperature is preferably 700-950°C, and in an embodiment of the present invention, it can be 700°C, 750°C, 800°C, 850°C, 900°C or 950°C. The holding time is preferably 8-24h, and in an embodiment of the present invention, it can be 8h, 10h, 12h, 15h, 18h, 20h, 22h or 24h. The rate of heating to the sintering temperature is preferably 3°C / min.

[0035] After the sintering is completed, the present invention preferably cools the obtained positive electrode material to room temperature.

[0036] The method provided by the present invention can realize the directional regulation of the crystal structure of layered oxides. The present invention divides the doping elements into two categories: elements with strong electronegativity and elements with weak electronegativity. Ti, Li and Fe are elements with weak electronegativity, and Mn and F are elements with strong electronegativity. The present invention adds the above elements during mixing. When the elements with strong electronegativity are introduced into the system, the mutual repulsion between atoms in the system becomes larger, thereby inducing the Na2O3 dual-phase structure in the system. x Ni a Cu bFe c Mn d O 2 The O3 phase in the system transforms into the P2 phase; when an element with weaker electronegativity is introduced into the system, the repulsion between atoms in the system will be weakened, thus inducing the Na2O3 dual phase in the system. x Ni a Cu b Fe c Mn d O 2 When the P2 phase in the system transforms into the O3 phase, the interlayer spacing becomes smaller, and more sodium ions will be deintercalated, so the initial capacity of the battery will become higher. When the O3 phase transforms into the P2 phase, the more Na ions in the O3 phase will be retained. + , but the interlayer spacing becomes wider, so it can make sodium ions easier to insert and remove without deforming the crystal structure, so the cycle stability will be better.

[0037] The preparation method provided by the present invention is simple and improves the comprehensive performance (e.g., first cycle discharge capacity and 100 cycle retention rate) and application potential of the positive electrode material. The sodium ion secondary battery using the positive electrode material of the present invention has a controllable crystal structure and can effectively reduce costs.

[0038] The present invention provides the sodium ion battery positive electrode material described in the above scheme or the use of the sodium ion battery positive electrode material prepared by the preparation method described in the above scheme in a sodium ion battery.

[0039] In order to further illustrate the present invention, a sodium ion battery positive electrode material provided by the present invention, a preparation method thereof and an application thereof are described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0040] Example 1 Sodium ion battery cathode material Na 0.85 [Ni 0.23 Cu 0.11 Fe 0.33 Mn 0.33 ] 0.95 Li 0.05 O 2 The preparation method is: The material sodium carbonate and the precursor Ni 0.23 Cu 0.11 Fe 0.33 Mn 0.33 (OH) 2(Refer to Example 1 in CN 116375111 A) and lithium carbonate are added to a grinding mortar in a molar ratio of 0.85:0.95:0.05, 10g of ethanol is added to dissolve the material, and the ethanol is completely volatilized, and then the resulting mixture is dried at 120°C, and then the dried material is placed in a tubular furnace and sintered in an air atmosphere, the sintering temperature is 850°C, the holding time is 10h, and the temperature is raised from room temperature at a heating rate of 3°C / min. After sintering is completed, the sodium ion battery positive electrode material is obtained after natural cooling to room temperature in air.

[0041] This embodiment provides a method for converting a two-phase P2 and O3 into a single phase O3, thereby converting the P2 phase in the system into the O3 phase.

[0042] Example 2 The difference from Example 1 is that lithium carbonate is replaced with titanium dioxide to obtain a sodium ion battery positive electrode material with a composition of Na 0.85 [Ni 0.23 Cu 0.11 Fe 0.33 Mn 0.33 ] 0.95 Ti 0.05 O 2 .

[0043] Example 3 The difference from Example 1 is that lithium carbonate is replaced with ferric nitrate to obtain a sodium ion battery positive electrode material with a composition of Na 0.85 [Ni 0.23 Cu 0.11 Fe 0.33 Mn 0.33 ] 0.95 Fe 0.05 O 2 .

[0044] Example 4 The difference from Example 1 is that lithium carbonate is replaced with manganese acetate to obtain a sodium ion battery positive electrode material with a composition of Na 0.85 [Ni 0.23 Cu 0.11 Fe 0.33 Mn 0.33 ] 0.95 Mn 0.05 O 2 .

[0045] This embodiment provides a method for converting a two-phase P2 and O3 into a single-phase P2, and converting the O3 phase in the system into the P2 phase.

[0046] Example 5 The difference from Example 1 is that manganese acetate is replaced with sodium fluoride to obtain a sodium ion battery positive electrode material with a composition of Na 0.85[Ni 0.23 Cu 0.11 Fe 0.33 Mn 0.33 ] 0.95 F 0.05 O 2 .

[0047] Comparative Example 1 The material sodium carbonate and the precursor Ni 0.23 Cu 0.1 Fe 0.33 Mn 0.33 (OH) 2 Add the mixture to a grinding mortar at a molar ratio of 0.85:1, add 10g of ethanol to dissolve the material, grind until the ethanol is completely volatilized, and then dry the resulting mixture at 120°C. Then put the dried material into a tube furnace and sinter it in an air atmosphere at a sintering temperature of 850°C, a holding time of 10h, and a heating rate of 3°C / min. After sintering, cool it naturally to room temperature in air to obtain a dual-phase structured sodium ion battery positive electrode material with a composition of Na 0.85 Ni 0.23 Cu 0.11 Fe 0.33 Mn 0.33 O 2 .

[0048] Structural characterization and performance testing 1. XRD test analysis The materials prepared in Example 1, Example 4 and Comparative Example 1 were subjected to XRD test analysis.

[0049] Figure 1 This is the XRD pattern of the positive electrode material of the O3 type sodium ion battery prepared in Example 1 of the present invention. Figure 1 It can be concluded from the XRD diagram that the positive electrode material of the sodium ion battery prepared after adding the Li element is O3 phase.

[0050] Figure 3 This is the XRD pattern of the P2 sodium ion battery positive electrode material prepared in Example 4 of the present invention. Figure 3 It can be concluded from the XRD diagram that the positive electrode material of the sodium ion battery prepared after adding the Mn element is the P2 phase.

[0051] Figure 5 This is the XRD pattern of the P2 / O3 dual-phase sodium ion battery positive electrode material prepared in Comparative Example 1 of the present invention. Figure 5 As shown, it can be seen that the sodium ion battery positive electrode material obtained in Comparative Example 1 is a dual phase of P2 and O3. The phase structures of the sodium ion battery positive electrode materials of Examples 1 to 5 and Comparative Example 1 are statistically shown in Table 1.

[0052] Table 1 Phase structures of the positive electrode materials for sodium ion batteries of Examples 1 to 5 and Comparative Example 1

[0053] In summary, Comparative Example 1 uses the same sintering procedure as Examples 1 to 5, but without doping any elements, and a sodium ion battery positive electrode material with a P2 / O3 dual-phase structure is obtained.

[0054] 2. SEM (Scanning Electron Microscope) Test Analysis The microstructure of all samples was further investigated by scanning electron microscopy (SEM).

[0055] Figure 2 This is a SEM image of the positive electrode material of the O3 type sodium ion battery prepared in Example 1 of the present invention. Figure 2 It can be seen from the SEM image that the positive electrode material of the sodium ion battery is mainly composed of microspheres composed of flakes, but the morphology of some flakes is not clear.

[0056] Figure 4 This is a SEM image of the positive electrode material of the P2 type sodium ion battery prepared in Example 4 of the present invention. Figure 4 From the SEM image, it can be seen that the positive electrode material of the sodium ion battery is clearly composed of microspheres in the form of flakes.

[0057] Figure 6 This is a SEM image of the P2 / O3 dual-phase sodium ion battery positive electrode material prepared in Comparative Example 1 of the present invention. Figure 6 As shown, the positive electrode material of sodium ion batteries is mainly composed of microspheres in the form of sheets.

[0058] 3. Electrochemical performance test Half-cell assembly: The sodium ion battery layered oxide positive electrode materials of Examples 1 to 5 and Comparative Example 1 were slurried with conductive carbon black (Super P) and polyvinylidene fluoride (PVDF) in a mass ratio of 9:0.5:0.5 in 1.6 g of N-methylpyrrolidone (NMP) solution under an inert atmosphere and coated on aluminum foil. After vacuum drying, they were cut into pole pieces with a diameter of 12 mm (with a loading of about 5 to 10 mg / cm 2 ). With the metal sodium sheet as the negative electrode, 1 mol / L NaClO 4 / polycarbonate (PC):ethylene carbonate (EC):dimethyl carbonate (DMC) (volume ratio 1:1:1) solution was used as the electrolyte and glass fiber was used as the separator diaphragm, which were assembled into CR2032 button cell half-cells in an argon glove box.

[0059] Charge and discharge test: The voltage range of the button half-cell charge and discharge is 2.0~4.1V. Before the cycle test, it is activated twice with a smaller current density of 15mA / g (0.1C), and then it is cycled at a rate of 1C in the same voltage range. All electrochemical performance tests are performed at room temperature. The electrochemical performance of the sodium ion battery positive electrode materials of Examples 1~5 and Comparative Example 1 is statistically shown in Table 2.

[0060] Table 2 Electrochemical properties of the sodium ion battery positive electrode materials of Examples 1 to 5 and Comparative Example 1

[0061] As can be seen from Table 2, the sodium ion battery positive electrode material obtained by the present invention has excellent electrochemical performance, a high first-cycle discharge capacity, and a high retention rate after 100 cycles.

[0062] 4.ICP test All sample materials were subjected to ICP testing to test the material composition in the samples. The test results are as follows: Table 3 Elemental composition of sodium ion battery positive electrode materials of Examples 1 to 5 and Comparative Example 1

[0063] Note that there is a certain difference between the above ICP test results and the results calculated according to the chemical formula, but this difference is within the allowable error range.

[0064] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A sodium ion battery positive electrode material, characterized in that: Composition: Na x [Ni a Cu b Fe c Mn d ] e M f O2, M includes Ti, Li, Fe, Mn or F; wherein, 0.67≤x≤1.2, 0≤a<0.3, 0≤b≤0.35, 0≤c≤0.35, 0.1≤d≤0.6, 0.8≤e≤1, 0<f≤0.2, a, b and c are not 0 at the same time, and a+b+c+d=1, e+f=1.

2. The sodium ion battery positive electrode material according to claim 1, characterized in that: The sodium ion battery positive electrode material is a layered structure.

3. The sodium ion battery positive electrode material according to claim 1 or 2, characterized in that: The sodium ion battery positive electrode material includes Na 0.85 [Ni 0.23 Cu 0.11 Fe 0.33 Mn 0.33 ] 0.95 Li 0.05 O2、Na 0.85 [Ni 0.23 Cu 0.11 Fe 0.33 Mn 0.33 ] 0.95 Ti 0.05 O2、Na 0.85 [Ni 0.23 Cu 0.11 Fe 0.33 Mn 0.33 ] 0.95 Fe 0.05 O2、Na 0.85 [Ni 0.23 Cu 0.11 Fe 0.33 Mn 0.33 ] 0.95 Mn 0.05 O2 or Na 0.85 [Ni 0.23 Cu 0.11 Fe 0.33 Mn 0.33 ] 0.95 F 0.05 O2.

4. The method for preparing the positive electrode material for a sodium ion battery according to any one of claims 1 to 3, characterized in that: The following steps are involved: Sodium salt, precursor Ni a Cu b Fe c Mn d (OH)2 and a compound containing element M are mixed and sintered to obtain the sodium ion battery positive electrode material; wherein 0≤a<0.3, 0≤b≤0.35, 0≤c≤0.35, 0.1≤d≤0.6, a, b and c are not 0 at the same time, and a+b+c+d=1; The element M includes Ti, Li, Fe, Mn or F.

5. The preparation method according to claim 4, characterized in that: The compound containing element M includes lithium carbonate, titanium dioxide, iron nitrate, manganese acetate or sodium fluoride.

6. The preparation method according to claim 4 or 5, characterized in that: The sintering temperature is 700-950° C., and the heat preservation time is 8-24 hours.

7. The preparation method according to claim 5, characterized in that: The sodium salt, the precursor Ni a Cu b Fe c Mn d The molar ratio of (OH)2 and the compound containing element M is (0.67~1.2):(0.8~1):(0~0.2), and is not zero.

8. The preparation method according to claim 4, characterized in that: The sodium salt includes sodium carbonate.

9. The preparation method according to claim 4, 5, 7 or 8, characterized in that: The mixing comprises: mixing sodium salt, precursor Ni a Cu b Fe c Mn d (OH)2, a compound containing element M and a polar organic solvent are mixed and ground until the polar organic solvent evaporates.

10. Use of the sodium ion battery positive electrode material according to any one of claims 1 to 3 or the sodium ion battery positive electrode material prepared by the preparation method according to any one of claims 4 to 9 in a sodium ion battery.

Citation Information

Patent Citations

  • F-doped P2-Na0.7MnO2 electrode material and preparation method thereof

    CN112830521A

  • Self-sodium-supplementing sodium ion battery positive electrode active material as well as preparation method and application thereof

    CN114790013A

  • Sodium ion positive electrode material, preparation method and sodium ion battery

    CN117154078A

  • Layered oxide positive electrode material and preparation method thereof, positive electrode plate, sodium ion battery and electric equipment

    CN117393748A

  • Single crystal sodium ion battery positive electrode material adopting fluxing agent method and preparation method of single crystal sodium ion battery positive electrode material

    CN118738372A